Individualized High-Protein Dietary Counseling During Chemotherapy in Gastrointestinal Cancer: A Systematic Review of Nutritional and Functional Outcomes - Febriana Intan Diatri; Abraham Guntur Bayu Aji; Ado Pranawalingga (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2026)
Gastrointestinal cancer patients frequently experience treatment-related anorexia, gastrointestinal toxicity, and metabolic stress during chemotherapy, placing them at high risk for malnutrition and muscle loss. Adequate protein intake is essential for maintaining muscle mass and functional capacity, yet many patients struggle to meet protein requirements without structured nutrition support. To evaluate the effects of individualized high-protein dietary counseling on nutritional and functional outcomes in adults with gastrointestinal cancers receiving chemotherapy. A systematic search of PubMed, Cochrane Library, and ScienceDirect identified interventional studies involving individualized dietary counseling aimed at improving protein intake. Eligible studies included adults with colorectal or gastric cancer undergoing chemotherapy or chemoradiotherapy and reported outcomes related to muscle mass, handgrip strength, or physical performance. Five studies met inclusion criteria and were synthesized narratively due to heterogeneity. All interventions led to improved energy and protein intake compared with usual care. Several studies reported significant improvements in nutritional status, PG-SGA scores, and serum albumin. One high-intensity intervention preserved skeletal muscle index and improved handgrip strength during adjuvant chemotherapy. Counseling also consistently enhanced quality of life, treatment tolerance, and symptom control. However, not all interventions prevented muscle loss, particularly in advanced disease or metastatic settings, highlighting the influence of disease burden and inflammation. Individualized dietary counseling exerts benefits through tailored symptom management, behavioral reinforcement, and sustained support for protein intake, even during periods of reduced appetite. These improvements may contribute to better clinical resilience and reduced treatment toxicity. Individualized high-protein dietary counseling is a valuable supportive care strategy for patients undergoing chemotherapy and should be integrated early in oncology practice.